Deteksi Pergerakan Kepala Menggunakan Metode Perbandingan Jarak Facial Landmark Untuk Pemilihan Menu Display - Zulfina Kharisma Frimananda; Fitri Utaminingrum (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Disability is every person who has limitations. One type of disability is a physical disability that is an abnormality in the hands, feet, or both. In general, all electronic devices such as joysticks, remotes, menu selections on the LCD, etc. still utilize the intermediaries of the hands to operate them. This is a problem for people with physical disabilities. This problem can be overcome by creating a system that can help persons with disabilities in selecting menus through the display by utilizing the movement of the head as a substitute for the function of the hand that cannot be used because of its disability. This system uses the Raspberry Pi as the processing unit while the implementation of the output of this system is the selection of menus on the display. Testing the accuracy of the movement and computing time of this system is carried out on ten people. The system produces an accuracy of 90% in the detection of head-to-right movements, accuracy of 100% in the detection of head-to-left movements, accuracy of 100% in the detection of head-up movements, accuracy of 100% in the detection of head-down movements, average the accuracy of each movement of the head to the right, left, up, and down to the integration of the menu display + model selection is 97.5% and the average computational time value on the condition of the head to the right movement is 770 ms, to the left is 776.9 ms, upwards is 771.8 ms, and to the left is 768.1 ms.